Sovereign bonds since Waterloo - Meyer, Josefin,Reinhart, Carmen M.,Trebesch, Christoph (Kiel Institute for the World Economy, 2021)
This paper studies external sovereign bonds as an asset class. We compile a new database of 266,000 monthly prices of foreign-currency government bonds traded in London and New York between 1815 (the Battle of Waterloo) and 2016, covering up to 91 countries. Our main insight is that, as in equity markets, the returns on external sovereign bonds have been sufficiently high to compensate for risk. Real ex-post returns average more than 6 percent annually across two centuries, including default episodes, major wars, and global crises. This represents an excess return of 3-4 percent above US or UK government bonds, which is comparable to stocks and outperforms corporate bonds. Central to this finding are the high average coupons offered on external sovereign bonds. The observed returns are hard to reconcile with canonical theoretical models and the degree of credit risk in this market, as measured by historical default and recovery rates. Based on our archive of more than 300 sovereign debt restructurings since 1815, we show that full repudiation is rare; the median creditor loss (haircut) is below 50 percent.
urn:nbn:de:101:1-2022031002170838185783
Keywords: Graue Literatur; Öffentliche Anleihe; Internationale Staatsschulden; Rendite; Risikoprämie; Wirtschaftsgeschichte; USA; Großbritannien